COVID-19 and HIV: Clinical Outcomes and Inflammatory Markers in a Cohort from a Reference Hospital in Rio de Janeiro, Brazil - Nathalia Beatriz Ramos de Sá; Karine Venegas Macieira; Mariana Rosa Inacio Coelho; Milena Neira Goulart; Marcelo Ribeiro-Alves; Leonardo Azevedo da Silva Rosadas; Kim Mattos Geraldo; Maria Pia Diniz Ribeiro; Sandra Wagner Cardoso; Beatriz Grinsztejn; Valdiléa G. Veloso; Andressa da Silva Cazote; et al. (Viruses)
Background: Severe COVID-19 presents a variety of clinical manifestations associated with inflammatory profiles. People living with HIV (PLWH) could face a higher risk of hospitalization and mortality from COVID-19, depending on their immunosuppression levels. This study describes inflammatory markers in COVID-19 clinical outcomes with and without HIV infection. Methods: We analyzed 112 inpatients of the Hospital Center for COVID-19 (INI/FIOCRUZ), including 22 cases of COVID-19 in PLWH (COVID/PLWH group). Plasma samples were tested for a panel of 15 cytokines by Luminex. Sociodemographic, clinical, and laboratory data were collected from patients’ clinical records. Results: COVID-19 individuals were stratified according to the WHO clinical severity profiles at hospitalization. Significant differences in clinical scores, symptoms (coughs), and the occurrence of HIV infection were found among the groups. Clinical blood parameters and plasma cytokines were analyzed among COVID-19 groups with distinct severity profiles. Critical COVID-19 cases showed higher levels of inflammatory markers (Bilirubin, D-dimer, PCR, and urea, as well as IL-8, IL-10, TNF-α, INF-α, IL-1β, IL-17A, IL-23, IL-6) than moderate and severe groups. The COVID/PLWH group had lower CD4 counts (64 cells/mm3) and cytokine levels than other COVID-19 patients. Conclusions: Overall, critically ill COVID-19 patients exhibited heightened inflammatory responses, while COVID/PLWH demonstrated unique immunological characteristics without increased mortality risk.